Aerobic exercise enhances mitochondrial homeostasis to counteract D-galactose-induced sarcopenia in zebrafish - Zhang-Lin Chen; Cheng Guo; Yun-Yi Zou; Chen Feng; Di-Xuan Yang; Chen-Chen Sun; Wei Wen; Zhen-Jie Jian; Zhe Zhao; Qin Xiao; Lan Zheng; Xi-Yang Peng; et al. (Experimental Gerontology, 2023)
Sarcopenia is a common skeletal muscle degenerative disease characterized by decreased skeletal muscle mass and mitochondrial dysfunction that involves microRNAs (miR) as regulatory factors in various pathways. Exercise reduces age-related oxidative damage and chronic inflammation and increases autophagy, among others. Moreover, whether aerobic exercise can regulate mitochondrial homeostasis by modulating the miR-128/insulin-like growth factor-1 (IGF-1) signaling pathway and can improve sarcopenia requires further investigation. Interestingly, zebrafish have been used as a model for aging research for over a decade due to their many outstanding advantages. Therefore, we established a model of zebrafish sarcopenia using d-galactose immersion and observed substantial changes, including reduced skeletal muscle cross-sectional area, increased tissue fibrosis, decreased motility, increased skeletal muscle reactive oxygen species, and notable alterations in mitochondrial morphology and function. We found that miR-128 expression was considerably upregulated, where as Igf1 and peroxisome proliferator-activated receptor gamma coactivator 1-alpha were significantly downregulated; moreover, mitochondrial homeostasis was reduced. Four weeks of aerobic exercise delayed sarcopenia progression and prevented the disruption of mitochondrial function and homeostasis. The genes related to atrophy and miR-128 were downregulated, Igf1 expression was considerably upregulated, and the phosphorylation levels of Pi3k, Akt, and Foxo3a were upregulated. Furthermore, mitochondrial respiration and homeostasis were enhanced. In conclusion, aerobic exercise improved skeletal muscle quality and function via the miR-128/IGF-1 signaling pathway, consequently ameliorating mitochondrial homeostasis in aging skeletal muscle.